Smoke-free homes programme : past, present and future - Precioso, J (2013)
Childhood exposure to Environmental Tobacco Smoke (ETS) is associated with serious health problems. Despite the recognised severity of childhood exposure to environmental tobacco smoke (ETS), several studies show high prevalence of exposed children in the world and also in Portugal. In order to protect children of this serious health hazard an ETS type preventive programme, “Smoke free-homes”, was developed and tested in Portugal. Its main purpose is to increase the number of parents who do not smoke and / or to reinforce the norm of not allowing smoking at home and in the car, enabling “participant students” to proactively promote parents’ behaviour change and effectively reduce or avoid ETS home exposure. This is a school based programme, to be applied in the classroom by teachers. A exposição das crianças ao Fumo Ambiental do Tabaco (FAT) está associada a graves problemas de saúde. Apesar da evidência científica sobre a gravidade da exposição das crianças ao FAT, muitos estudos mostram que existe uma elevada percentagem de crianças expostas ao FAT no Mundo (aproximadamente 50%) e também em Portugal (40% segundo alguns estudos realizados). Com o objectivo de proteger as crianças desta agressão, foi desenhado em Portugal o programa de prevenção denominado “Domicílios Livres de Fumo”. A sua principal finalidade é aumentar a prevalência de pais e mães que não fumam (e/ou não permitam que se fume) em casa e no carro. O programa foi desenhado para ser aplicado nas salas de aulas, pelos professores.